The Hard Task of Hitting the Mean: Aristotle’s Mean (Mesotes) and Buddha’s Middle Path (Majjhima Patipad) - Lyssenko, Viktoria (Acta Orientalia Vilnensia, 2002)
The author compares Aristotle with the Buddha who, though incompatible with one another in their mode of thought (Aristotle was a theoretical thinker, inquiring into those very matters which the Buddha, as a practical religious thinker, considered to be completely futile), agreed at least about one point: they clearly realised the extreme difficulty of attaining the mean (or the middle), both understood it as something more complex than an equal distance from opposite ends, or an arithmetical mean, or a mechanical equilibrium (equipoise). They presented the mean regarding human beings as a state which is never given a priori, established spontaneously, or found by pure chance, but, on the contrary, is the subject of a constantly renewable creative search. The comparison is based on the analysis of Aristotle’s texts (Eud. Eth., Nic. Eth., etc.) and the Buddhist texts from the Pali Canon (Vinaya pitaka and Sutta pitaka).